(untitled) - The World Bank in Vietnam (WB) (Hà Nội, 2003)
The overall objective of the Forest Protection and Rural Development Project is to assist Vietnam to protect and manage natural forests with high biodiversity. More specifically, the main development objectives are: 1) to effectively protect Cat Tien National Park (CTNP) and to effectively protect and manage the Chu Mom Ray Nature Reserve (CMRNR); 2) to effectively manage the remaining natural forests outside the protected areas (PA) but within the buffer zone of CTNP and CMRNR; 3) to reduce dependency on CTNP and CMRNR for subsistence and cash income; and 4) to strengthen capacity of the government to effectively design, implement, and monitor ICDPs. To achieve these objectives, three main components and their subcomponents comprise the project. The Protected Area Management for CMRNR Component provides for revising the existing Management Plan for CMRNR in two phases; implements the revised Management Plan including boundary demarcation, introduces PA management programs, supports basic infrastructure, and supplies basic equipment; implements selected research studies and surveys; formulates and implements a public awareness campaign in the CMRNR; develops programs to encourage and manage nature tourism in the PA and buffer zone; and trains PA staff to run the intensified conservation management and visitor programs. The Buffer Zone Development Component has six subcomponents: community development planning, land allocation involving land use planning at the commune level and helping to prepare cadastre maps and the issuance of land use certificates; social support in the form of "food security," basic infrastructure and activities to strengthen local social and cultural institutions; agricultural support services (extension, technology transfer, and public awareness); forest protection and management; and rural infrastructure improvement, including expanding irrigation systems, upgrading roads, and improving road access. The third component, Project Management and Institutional Development, includes strengthening institutional capacity at all levels to implement project activities and sustain project interventions.
Keywords: Rural development,Phát triển nông thôn,Rural development projects,Dự án phát triển nông thôn; Economic conditions,Điều kiện kinh tế; Vietnam,Việt Nam,Vietnam,Việt Nam